Convergence and Overtaking in a Dynamic Two Country Model - Partha Sen; Koji Shimomura (Center for Economic Studies and ifo Institute (CESifo), 2016)
In two-sector infinite-horizon trade models with factor–price-equalization, convergence of aggregate capital-labor ratios and incomes does not occur because the Euler equations imply equal growth rate of consumption in all economies. In a two-country dynamic specific factors model, we show that factor–price-equalization occurs only in the long run. Per capita incomes and consumptions do not necessarily converge. These depend on the endowments of the primary factors. Depending on these endowments, an initially poorer economy may end up as the richer economy in the steady state, overtaking the initially richer one.
Keywords: F11; 330; convergence; specific factors; Euler equations